(untitled) (Third Sector Social Economic Review, 2025)
Nowadays, the concepts of green transformation and green marketing play a critical role in addressing environmental problems and meeting consumer demands, and businesses are adopting the concept of social marketing by developing strategies that consider not only profit but also environmental concerns. A review of recent literature reveals that the concept of green marketing is supported by various studies aimed at strengthening the position of sustainable products and services in the consumer market. However, the increase in the number of studies focusing on these issues has also revealed the need for their systematic analysis. This study aims to explore emerging trends and future outlook in green transformation and green marketing literature through a bibliometric analysis of academic studies. To this end, bibliometric analysis was employed in this descriptive study to assess the productivity and impact of existing research via performance analysis and to uncover knowledge clusters using science mapping. A total of 421 articles from the Web of Science (WOS) database were analyzed using the RStudio-based Biblioshiny program. Bibliometric methods were used to analyze key topics, influential researchers and publications, author productivity, citation counts, and interrelationships among these factors. As a result of the analyses; although green transformation and green marketing are associated with various subheadings, it is seen that the most frequently used keywords by the authors are "circular economy", "sustainable consumption" and "sustainability". The Journal of Cleaner Production (3302 citations) ranked first among the international journals with the most studies. According to the institutional affiliations of the main authors, China, England and Italy were the top three countries with the highest number of publications. The rates of international co-operation in publications from these countries are also noteworthy.